Contemporary management strategies of blunt tracheobronchial injuries. (March 2021) - Rieth, Anna; Varga, Endre; Kovács, Tamás; Ottlakán, Aurél; Németh, Tibor; Furák, József
Highlights: Tracheobronchial injuries are rare but can become life-threatening conditions. A prompt diagnosis and early management can be lifesaving. We offer an algorithmic of management and summarize the most important steps according to literature. A high index of suspicion is required for diagnosis with most common symptoms being respiratory distress, subcutaneous emphysema and pneumothorax. As CT is less informative, early laryngo- or bronchoscopic examination and prompt intubation below the site of the injury have priority. Primary anastomosis is required with minimal resection. Earlier postoperative extubation leads to a better outcome. Abstract: Background: Tracheobronchial injuries are rare but feasibly life-threatening conditions. A prompt diagnosis and early management can be lifesaving. Due to the unspecific symptoms and indirect radiological signs the diagnosis often delays. Objectives: We present a short series of patients suffering from tracheobronchial airway laceration. All the three patients had blunt thoracic or neck trauma and showed early signs of tracheobronchial injury. In the first case a 44-year-old woman was crushed by a bus. Subcutaneous emphysema, pneumothorax on chest computed tomography and hypoxaemia despite of chest tube suggested the presence of an airway injury. During operation a 4-cm-long tear of the trachea and a complete transection of the right main bronchus were found. In the second case a 12-year-old girl was crossed by a truck trailer. Early signs were respiratory failure, extended subcutaneous emphysema, blood clot in the larynx, pneumothorax on both sides. Chest CT showed pneumomediastinum. During the operation a longitudinal laceration was found separating the two main bronchi at the bifurcation. In the third case a 9-year-old boy was injured in a car accident, when the seat-belt crossed his neck. Spreading subcutaneous emphysema, pneumomediastinum and an overinflated endotracheal tube's cuff were found on CT. A completely transected trachea between the first and second tracheal rings was found. All three patients required fast intubation and bronchoscopic examination to confirm the diagnosis, and to identify the site of lacerations. All the patients underwent primary reconstruction and recovered successfully. Conclusions: In case of suspected tracheobronchial injury, a high index of suspicion is required for early diagnosis. Most commonly respiratory distress, subcutaneous emphysema and pneumothorax are found on physical examination. Prompt intubation below the site of the injury and early laryngo- or bronchoscopic examination have priority, as we did in our cases. A primary anastomosis is required with minimal resection during urgent operation. A better outcome is to be expected when extubation is done early after surgery. We offer ordinal steps that should be taken to lead to a prompt management and good long-term outcome based on the literature and our experiences.